Diagnostic value of plasma chromogranin A levels for pheochromocytoma - CUI Hao, QIN Wuyao, WANG Jinyao, SHANG Jiwen (Zhongguo linchuang yanjiu, 2024)
Objective To investigate the role of plasma chromogranin A (CgA) and free metanephrines (MNs) levels in the diagnosis of pheochromocytoma (PHEO). Methods The clinical data of 26 patients with PHEO (PHEO group) and 31 patients with other adrenal tumors (non-PHEO group) admitted to Shanxi Bethune Hospital from January 2021 to January 2023 were analyzed retrospectively. The preoperative plasma CgA levels were compared between PHEO patients and non-PHEO patients, and the changes of plasma CgA levels of PHEO patients were compared between postoperative and preoperative. The receiver operating characteristic curve (ROC curve) was used to analyze the diagnostic efficacy of the plasma CgA，MNs levels and their combination on PHEO. Results Preoperative plasma CgA level of patients in the PHEO group was significantly higher than that in the non-PHEO group ［(647.8±196.2) ng/mL vs (96.4±34.1) ng/mL， t=14.15， P＜0.01］. Compared to the preoperative level, the postoperative plasma CgA in the PHEO group was significantly reduced ［(114.8±60.5) ng/mL vs (647.8±196.2) ng/mL, t=12.78， P＜0.01］. ROC curve analysis results showed that the AUC of CgA and MNs for the diagnosis of PHEO were 0.988 and 0.940, and the cutoff values were 183.1 ng/mL and twice the upper limit of the reference interval,respectively,with sensitivity of 100% and 84.6%, and specificity of 87.1% and 93.5%, respectively; the combined AUC of the two was the highest, at 0.994. Conclusion Plasma CgA levels have a high diagnostic value in patients with PHEO,and can be used as a complementary indicator of plasma MNs for the diagnosis of PHEO to improve diagnostic accuracy."